PENGARUH EARNING PER SHARE, LEVERAGE, DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS - Lutfiyani, Amila; Mahpudin, Endang (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the impact of Earning Per Share (EPS), leverage, and liquidity on the likelihood of financial distress, which is measured using the Altman Z-Score method, based on data available from the annual financial reports for the period 2021–2023 obtained from the official IDX website (www.idx.co.id) and the respective companies. The dependent variable in this research is financial distress, while the independent variables are earning per share, leverage, and liquidity. The sampling technique used is purposive sampling, resulting in 10 companies being selected as samples, with a total of 30 observational data points. Data analysis was conducted using multiple linear regression with the assistance of SPSS Version 25 statistical software. The results indicate that the variables Earning Per Share and leverage have a significant effect on financial distress, whereas the liquidity variable does not show a significant effect on financial distress.